2011
DOI: 10.1080/02664763.2010.545119
|View full text |Cite
|
Sign up to set email alerts
|

Features and performance of some outlier detection methods

Abstract: A review of several statistical methods that are currently in use for outlier identification is presented, and their performances are compared theoretically for typical statistical distributions of experimental data, considering values derived from the distribution of extreme order statistics as reference terms. A simple modification of a popular, broadly used method based upon box-plot is introduced, in order to overcome a major limitation concerning sample size. Examples are presented concerning exploitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 27 publications
2
87
0
Order By: Relevance
“…Therefore, the indentation size effect results to be negligible in the investigated macro hardness range [9]. In conclusion, it is possible to estimate the measurement reproducibility of the indentation modulus according the three methods for evaluating S. In case of LEM and authors' methods, once identified and eliminated outliers [31], the standard deviations of the values of E IT are taken as measurement reproducibility; these values are respectively 6.74 kN/mm 2 and 7.14 kN/mm 2 . Instead, in case of PLM, it is considered the standard deviation of residuals with respect to the model in Eq.…”
Section: 2mentioning
confidence: 97%
“…Therefore, the indentation size effect results to be negligible in the investigated macro hardness range [9]. In conclusion, it is possible to estimate the measurement reproducibility of the indentation modulus according the three methods for evaluating S. In case of LEM and authors' methods, once identified and eliminated outliers [31], the standard deviations of the values of E IT are taken as measurement reproducibility; these values are respectively 6.74 kN/mm 2 and 7.14 kN/mm 2 . Instead, in case of PLM, it is considered the standard deviation of residuals with respect to the model in Eq.…”
Section: 2mentioning
confidence: 97%
“…‱ Based on the sample mean and standard variance, IQR is less vulnerable to extreme values than other filtering methods because it uses quartiles that are resistant to extreme values (Walfish, 2006); (Barbato, Barini, Genta & Levi, 2011).…”
Section: Outlier Filteringmentioning
confidence: 99%
“…Evidence of rather abusive exclusion of outliers appears for both IQR and Chauvenet's methods [16], suggesting an empirical distribution shape radically deviating from the original data set. On the other hand, by retaining a few borderline experimental values, modified IQR, Grubbs' and the extreme values method manage to preserve some typical features of the original data set, while at the same time effectively shielding estimates of main population parameters -central tendency, and scatter -from outlier induced bias.…”
Section: Identification and Treatment Of Outliersmentioning
confidence: 99%
“…Fig.3 shows normal probability plots of values of coded gravity acceleration; at either tail a number of discordant results may be observed, mainly traceable to such anomalies as referred to above. Outliers are identified according to Chauvenet's, Grubbs', and IQR (interquartile range) methods; another based upon extreme value distribution [15], and a modification of IQR method were also considered [16], see also [2], [17].…”
Section: Metrological Problems In Absolute Measurement Of Gravity Accmentioning
confidence: 99%